Main categories of functional particles in Arabic grammar and their features - badache, ali (El Omda in Linguistics and Discourse Analysis, 2022)
This article addresses the main categories of functional particles in Arabic grammar and their features, aiming to examine them and identify their distinctive characteristics. The basic principle is that meanings are expressed through particles; therefore, each meaning was assigned a primary particle that indicates it from the outset, known as the “principal particle” (umm al-bāb). This particle shares features with its counterparts within the same category, while also exceeding them in certain characteristics. The remaining particles in the same category are then interpreted in relation to it. Grammarians observed this pattern and accordingly classified these principal particles into categories such as interrogation, condition, exception, particles governing the subjunctive and jussive moods of the verb, inna and its sisters, coordination, and vocative particles. The conclusion is that the categories of functional particles in Arabic possess principal elements characterized by generality of usage, frequency, simplicity, originality, flexibility, and interpretive authority over other particles in the same category, with grammarians unanimously agreeing on their status as true particles.